Tree Species Richness and Neighborhood Effects on Ectomycorrhizal Fungal Richness and Community Structure in Boreal Forest - Otsing, Eveli; Anslan, Sten; Ambrosio, Elia; Koricheva, Julia; Tedersoo, Leho (Frontiers in Microbiology, 2021)
Tree species identity is one of the key factors driving ectomycorrhizal (EcM) fungal richness and community composition in boreal and temperate forest ecosystems, but little is known about the influence of tree species combinations and their neighbourhood effects on EcM communities. To advance our understanding of host plant effects on EcM fungi, the roots of silver birch, Scots pine and Norway spruce were analyzed using high-throughput sequencing across mature boreal forest exploratory plots of monocultures and two- and three-species mixtures in Finland. Our analyses revealed that tree species identity was an important determinant of EcM fungal community composition, but tree species richness had no significant influence on EcM fungal richness and community composition. We found that EcM fungal community composition associated with spruce depends on neighbouring tree species. Our study suggests that at a regional-scale tree species identity is the primary factor determining community composition of root-associated EcM fungi alongside with tree species composition effects on EcM fungal community of spruce in mixed stands.